PELATIHAN KADER KESEHATAN DALAM DETEKSI DINI DAN PENCEGAHAN STUNTING DI WILAYAH PUSKESMAS KARANG INTAN 2 KABUPATEN BANJAR - Megawati, Megawati; Isrowiyatun Daiyah (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
Reducing the prevalence of stunting is a priority of the Sustainable Development Goals (SDG's) in Indonesia until 2030 to reduce as much as 40% of the number of stunted toddlers (Kemenkes RI, 2018; WHO, 2018). The national target for stunting prevalence is set at l4% (fourteen percent) by 2024 (PP RI, 2021). To detect and prevent stunting, cooperation from various stakeholders is needed, especially those related to child nutrition and health. The relevant stakeholders are not only health workers but also health cadres. Posyandu cadres as people who are also close to the community and are an extension of health workers in terms of dealing with maternal and child health problems found in the community can be very strategic to be used as parties who can help overcome the problem of stunting according to their capacity. Based on this, we intend to intervene with health cadres as promoters of stunting prevention and early detection in Karang Intan Sub-district as a sub-district with a high stunting rate in Banjar District. Health cadres will be provided with training, and then they are expected to apply their knowledge to the community, especially prospective mothers, new mothers and mothers with toddlers to care about stunting and prevent stunting